2021 IEEE International Symposium on Circuits and Systems (ISCAS) 2021
DOI: 10.1109/iscas51556.2021.9401381
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Channel Dimensions Attention Feature Transfer for Better Convolutional Neural Networks

Abstract: Knowledge distillation is an extensively researched model compression technology, which uses a large teacher network to transmit information to a small student network. The critical point of the knowledge distillation method to improve the performance of the student network is to find an effective method to extract the information from the feature. The attention mechanism is a widely used feature processing method to process features effectively and obtain more expressive information. In this paper, we propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Recent studies have shown that optimizing spatial dimension information can improve the performance of the network [43]. The SE attention module added allows the network to calibrate the importance of the channel adaptively.…”
Section: Extended Se Attention Modulementioning
confidence: 99%
“…Recent studies have shown that optimizing spatial dimension information can improve the performance of the network [43]. The SE attention module added allows the network to calibrate the importance of the channel adaptively.…”
Section: Extended Se Attention Modulementioning
confidence: 99%
“…It has been proved that correlation between channels and spatial dimensions in the feature map can be completely decoupled [ 42 ]. Thus, separating ordinary convolutions can significantly reduce parameters and training time.…”
Section: Methodsmentioning
confidence: 99%
“…It selects the key area of the image and gears the focus of the model. CBAM is a feed-forward model whereby the starfish images are analysed from two dimensions namely channel and spatial [34]. The spatial attention is used to search the area where the attention needs to be focussed in the starfish feature map.…”
Section: Proposed Optimised Cnn Modelsmentioning
confidence: 99%